Representasi Alam dan Lingkungan pada Cerita Jagapati Bumi sebagai Media Edukasi Ekologis bagi Remaja - Faizah, Dian Arifatul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to explore environmental problems that are currently increasingly urgent to be resolved. Ecological education is a main means of building environmental awareness, especially among teenagers. The book Jagapati Bumi by Anna Farida offers an innovative approach to communicating environmental knowledge through myths and local wisdom. This research uses a descriptive qualitative approach to analyze the representation of nature in the story Jagapati Bumi as a literary environmental study. The results of the analysis show that the myths in this book not only function as entertainment, but also as educational media that instill the values ​​of environmental conservation. Through a narrative that describes the harmonious relationship between humans and nature, this book invites readers to respect and preserve the environment. In this way, Jagapati Bumi plays an important role in forming the character of teenagers who care about environmental sustainability, as well as developing deep ecological awareness. This research confirms that literature based on local wisdom can be an effective tool for educating and encouraging pro-environmental actions among teenagers.